MEDIA AUDIO CERITA BINATANG TERHADAP KETERAMPILAN MENYIMAKANAK AUTIS KELAS 1 - DASIANA, (Jurnal Pendidikan Khusus, 2016)
ABSTRACTThe communication and language obstacles experienced by the autism children was scrutinizing skill such as not responding to the question, having difficulty in following the oral instruction, understanding symbol language, imitating sentence or song, less understanding language, and appearing misunderstanding the word meaning.Based on the obstacle above, the research about “could scrutinizing skill be influenced by using audio media of animal story to autism children of class I in SLB Harmoni Gedangan Sidoarjo?” would be done. This research purpose was to test the influence of using audio media of animal story toward scrutinizing skill to autism children of class I in SLB Harmoni Gedangan Sidoarjo.This research used quantitative approach and pre experiment kind with “One Group Pretest-Posttest Design”. The data collection method used test to collect the data of scrutinizing skill result before and after giving intervention and the data analysis technique used statistic non parametric of sign test. The result of data analysis indicated Zh = 2,05 > Z table = 1,96 to significant level 5% (two sides test) so it could be concluded that there was significant influence of audio media of animal story toward scrutinizing skill to autism children of class I in SLB Harmoni Gedangan Sidoarjo.Keywords: Audio media of animal story, scrutinizing skill, autism children